Platanus orientalis (Plane Tree) Extract Protects Against Hyperoxaluria Induced Kidney Damage - ŞEN, ALİ; ŞENER, TARIK EMRE; ŞENKARDEŞ, İSMAİL; ERTAŞ, BÜŞRA; ÇETİNEL, ŞULE (My University, 2022)
The aim of this study is to determine whether Platanus orientalis (PO) which has anti-inflammatory, antioxidant and diuretic properties and used in the treatment of kidney stones as traditional folk medicine, will reduce or prevent the stone formation in the urinary system. To simulate the urolithiasis model 0.75% ethylene glycol (EG) and 1% ammonium chloride (AC) were applied to Sprague-Dawley rats. The rats were divided into four groups (n=8). The control group was given standard drinking water for 5 weeks. EG group received 0.75% EG in their drinking water containing 0.75% EG and 1% AC. PO extract (100 mg/kg) was given orally for 5 weeks to the preventive group and for last 2 weeks to the therapeutic group, respectively. At the end of experiment, 24-hour urine and kidney samples were obtained. In urine samples, calcium and citrate levels were decreased and oxalate level was increased in the EG group. In kidney samples myeloperoxidase, caspase-3, N-acetyl-β-glycosaminidase (NAG) activities, malondialdehyde (MDA), 8-hydroxy-2-deoxyguanosine (8-OHdG), tumor necrosis factor-α and interleukin-1β levels were increased while superoxide dismutase activity and glutathione levels were decreased in the EG group. These biochemical parameters returned to control levels in both PO treatment groups. Histological findings also correlate with these results. Our findings are suggested that PO treatments is effective in both preventive and therapeutic groups.
Keywords: Platanus orientalis; kidney stone; urolithiasis; rat